Sea surface temperature estimates for sediment cores in the Japan Sea - Frederike Wittkopp; Masanobu Yamamoto; Heiko Moossen; Tom Dunkley Jones; Andrew C G Henderson; James A Bendle (PANGAEA, 2017)
Organic sea surface temperature proxies, UK extquotesingle37 and TEX86, were used to reconstruct sea surface temperatures in the Japan Sea for the last 17 million years. Data was generated from IODP Expedition 346 (Site U1425) and Expedition 127/128 (Site 797).